2020
DOI: 10.1302/2058-5241.5.200041
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of virtual fracture clinics in orthopaedic trauma in the UK during the coronavirus crisis

Abstract: Virtual fracture clinics (VFC) are advocated by new orthopaedic (British Orthopaedic Association) and National Health Service (NHS) guidelines in the United Kingdom. We discuss benefits and limitations, reviewing the literature, as well as recommendations on introducing a VFC service during the coronavirus pandemic and into the future. A narrative review identifying current literature on virtual fracture clinic outcomes when compared to traditional model fracture clinics in the UK. We identify nine relevant pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Virtual fracture clinics (VFCs) have been widely implemented in the UK and Republic of Ireland as an alternative to traditional fracture clinic attendance 6 . The original model published by the Glasgow Royal Infirmary consisted of direct emergency department (ED) discharge of simple stable injuries including fifth metacarpal, radial head, metatarsal and stable ankle fractures, and VFC review of remaining conditions not requiring admission 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Virtual fracture clinics (VFCs) have been widely implemented in the UK and Republic of Ireland as an alternative to traditional fracture clinic attendance 6 . The original model published by the Glasgow Royal Infirmary consisted of direct emergency department (ED) discharge of simple stable injuries including fifth metacarpal, radial head, metatarsal and stable ankle fractures, and VFC review of remaining conditions not requiring admission 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in non-attendance of almost 75% was noted. They also noted that VFCs do not impede the training and education of trainees [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent articles have described the rapid adoption and evolution of VFC services during the pandemic. 9 , 17 - 20 The general principles of the VFC model as outlined by the original centre remain the same. 2 , 9 , 12 However, there is variation in practice across the UK, including the grade of staff making management decisions, provision of verbal and written information, and local treatment protocols for specific injuries.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 17 - 20 The general principles of the VFC model as outlined by the original centre remain the same. 2 , 9 , 12 However, there is variation in practice across the UK, including the grade of staff making management decisions, provision of verbal and written information, and local treatment protocols for specific injuries. 12 Prior to the pandemic, several studies have reported good acceptability of the VFC model in their local centres in the management of specific injuries, such as fifth metacarpal fractures, 3 , 21 fifth metatarsal fractures, 3 , 22 clavicle fractures, 23 mallet finger injuries, 24 and ankle fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation